Appraising risk in active surveillance of localized prostate cancer. (16th May 2019) - Hogden, Anne; Churruca, Kate; Rapport, Frances; Gillatt, David
Abstract: Objectives: Men diagnosed with low‐risk prostate cancer are typically eligible for active surveillance of their cancer, involving monitoring for cancer progression and making judgements about the risks of prostate cancer against those of active intervention. Our study examined how risk for prostate cancer is perceived and experienced by patients undergoing active surveillance with their clinicians, how risk is communicated in clinical consultations, and the implications for treatment and care. Method: Participants were nine patients and three clinicians from a university hospital urology clinic. A staged, qualitative, multi‐method data collection approach was undertaken, comprising: observations of consultations; patient and clinician interviews; and patient surveys. The three data sets were analysed separately using thematic analysis and then integrated to give a comprehensive view of patient and clinician views. Results: Thirty data points (eight patient surveys; 10 observations of consultations between patients and clinicians; 10 patient interviews; and two clinician interviews) combined to create a detailed picture of how patients perceived and appraised risk, in three themes of "Making sense of risk", "Talking about risk" and "Responding to risk". Conclusion: Effective risk communication needs to be finely tuned and timed to individual patient's priorities and information requirements. A structured information exchange process that identifies patients' priorities, and details key moments in risk assessment, so that complexities of risk are discussed in ways that are meaningful to patients, may benefit patient care. These findings could inform the development of patient‐centric risk assessment procedures and service delivery models in prostate cancer care more broadly.